Intake and utilization of feed by work oxen - Soller, H.; Reed, J.D.; Butterworth, M.H. (International Livestock Centre for Africa, 1986)
Presents findings of a study conducted to determine changes in feed intake and utilization by oxen during work, comparing estimated energy balance and liveweight change in local zebu and crossbreds. Also assesses breed effects on water intake, feed intake and utilization.